2010
DOI: 10.1111/j.1467-629x.2010.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Narratives in managers’ corporate finance decisions

Abstract: This article uses the extended case method to explore senior executives' corporate finance decisions. We quantified firm's finance practices using a mail survey, and then -to resolve puzzles in managers' decision processes -conducted faceto-face interviews with chief finance officers of large listed firms. The interviews identified six themes as consistent influences on finance decisions: pressures imposed by clienteles; constraints on resources; risk management; heuristics; real options; and sustainability. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…These include, among others, “start small, grow big organically,” “minimize initial investments,” “repeat successes to take full advantage of them,” and “sharing is the way to loyalty and prosperity. Give everyone his due.” Coleman, Maheswaran, and Pinder (), who have worked on narratives for decisions in corporate finance, listed a number of similar verbal heuristics, such as “focus on keeping it simple and understand what are the fundamental things you have got to get right.” Verbal approaches such as these can provide valuable insights into how heuristics are part of everyday managerial decision making. However, these approaches share the problem of producing a large unstructured body of very specific heuristics without stating when and why they perform well.…”
Section: Managerial Heuristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, among others, “start small, grow big organically,” “minimize initial investments,” “repeat successes to take full advantage of them,” and “sharing is the way to loyalty and prosperity. Give everyone his due.” Coleman, Maheswaran, and Pinder (), who have worked on narratives for decisions in corporate finance, listed a number of similar verbal heuristics, such as “focus on keeping it simple and understand what are the fundamental things you have got to get right.” Verbal approaches such as these can provide valuable insights into how heuristics are part of everyday managerial decision making. However, these approaches share the problem of producing a large unstructured body of very specific heuristics without stating when and why they perform well.…”
Section: Managerial Heuristicsmentioning
confidence: 99%
“…Give everyone his due. " Coleman, Maheswaran, and Pinder (2010), who have worked on narratives for decisions in corporate finance, listed a number of similar verbal heuristics, such as "focus on keeping it simple and understand what are the fundamental things you have got to get right." Verbal approaches such as these can provide valuable insights into how heuristics are part of everyday managerial decision making.…”
Section: Managerial Heuristicsmentioning
confidence: 99%
“…Coleman et al . () use management surveys and interviews to show that Australian CFOs are impacted in their financial decisions by pressure from expectations of different stakeholder groups. AuYong et al .…”
Section: Share Repurchases In Australiamentioning
confidence: 99%
“…In support of this, 54% of respondents in the survey conducted by Coleman et al . () indicated that the level of franking credits available to be paid out to shareholders was considered important in the decision to undertake a buyback.…”
Section: Payout Policymentioning
confidence: 99%
See 1 more Smart Citation